2014
DOI: 10.1155/2014/956369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Radial Shortening Osteotomy and Vascularized Bone Graft in Kienböck’s Disease

Abstract: The aim of this study was to compare two surgery methods including radial shortening and radial shortening combined with vascularized bone graft for treatment of stage II or IIIa of Kienböck's disease. It is a randomized, controlled clinical trial, which was carried out in 2011–2013. Twenty-four patients were assigned equally to radial shortening group (A) or radial shortening combined with vascularized bone graft group (B). The outcome was assessed by Mayo Wrist score before and 9 months after surgery. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Dehghani et al concluded from their randomized study that a combination of radial shortening and vascularized bone grafting is more efficient than shortening alone in terms of Mayo Wrist Score. 26 The follow-up in that study was only 9 months. Table 4 summarizes the literature on outcome of radial shortening osteotomy for symptomatic Kienböck's disease with average follow-up duration of more than 10 years.…”
Section: Discussionmentioning
confidence: 90%
“…Dehghani et al concluded from their randomized study that a combination of radial shortening and vascularized bone grafting is more efficient than shortening alone in terms of Mayo Wrist Score. 26 The follow-up in that study was only 9 months. Table 4 summarizes the literature on outcome of radial shortening osteotomy for symptomatic Kienböck's disease with average follow-up duration of more than 10 years.…”
Section: Discussionmentioning
confidence: 90%
“… 10 , 11 , 12 , 13 One study reported 2 mm of shortening, two studies reported an RS of up to 2 mm and 3 mm, and one study reported 2–5 mm of shortening. 14 , 15 , 16 , 17 One study performed RS to achieve neutral to (−1) ulnar variance. 18 …”
Section: Resultsmentioning
confidence: 99%
“…In these studies, radial shortening is considered the treatment of choice for stage I to IIIA of Kienböck's disease. 7,[15][16][17] On the other hand, capitate shortening can reduce pain and enhance the wrist's function and ROM and grip strength effectively. The result of the current trial is consistent with the results of the studies by Schuind et al 7 and Cross and Matullo.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, radial shortening is considered the treatment of choice for stage I to IIIA of Kienböck’s disease. 7,15-17…”
Section: Discussionmentioning
confidence: 99%